A Tris(3‐pyridyl)stannane as a Building Block for Heterobimetallic Coordination Polymers and Supramolecular Cages. Issue 61 (9th October 2019) - Yang, Eric S.; Plajer, Alex J.; García‐Romero, Álvaro; Bond, Andrew D.; Ronson, Tanya K.; Álvarez, Celedonio M.; García‐Rodríguez, Raúl; Colebatch, Annie L.; Wright, Dominic S.
Abstract: The systematic assembly of supramolecular arrangements is a persistent challenge in modern coordination chemistry, especially where further aspects of complexity are concerned, as in the case of large molecular mixed‐metal arrangements. One targeted approach to such heterometallic complexes is to engineer metal‐based donor ligands of the correct geometry to build 3D arrangements upon coordination to other metals. This simple idea has, however, only rarely been applied to main group metal‐based ligand systems. Here, we show that the new, bench‐stable tris(3‐pyridyl)stannane ligand PhSn(3‐Py)3 (3‐Py=3‐pyridyl) provides simple access to a range of heterometallic Sn IV /transition metal complexes, and that the presence of weakly coordinating counter anions can be used to build discrete molecular arrangements involving anion encapsulation. This work therefore provides a building strategy in this area, which parallels that of supramolecular transition metal chemistry. Abstract : Simply supra : The new, bench‐stable tris(3‐pyridyl)stannane ligand PhSn(3‐Py)3 (3‐Py=3‐pyridyl) provides simple access to a range of heterometallic Sn IV /transition metal complexes (see figure). Discrete molecular arrangements involving anion encapsulation are observed in the presence of weakly coordinating anions, whereas coordination polymers are formed where coordinating anions are involved.